Enhancement of skyrmion density via interface engineering - Bhatti, Sabpreet (2023)
Magnetic skyrmions are promising candidates for computing and memory applications. The static and dynamic behaviors of skyrmions are tunable by altering the interfacial magnetic properties. These interfacial magnetic properties are alterable by modifying the interface structure of thin films. However, the relationship between the structural properties of the interface and the skyrmions properties is not straightforward, and a comprehensive insight is required to facilitate better controllability of the skyrmions’ behaviors. Here, we comprehensively understand the relationship between atomic displacements at the interface and skyrmions’ static behavior. In this study, we used ion irradiation to achieve inter-atomic displacements. We observed that the inter-atomic displacements could tailor the physical properties of skyrmions. We noticed a peculiar increase in the magnetization, Dzyaloshinskii-Moriya interaction, and exchange stiffness. The modifications in magnetic properties reduced the domain wall energy, which enhanced the skyrmion density (by six-folds) and reduced the average skyrmion diameter (by 50%). Furthermore, we compared the observed results of ion irradiation with those from the annealing process (a well-studied method for modifying magnetic properties) to better understand the effect of atomic displacements. Our study provides a route to achieve a highly-dense skyrmion state, and it can be explored further to suppress the skyrmion Hall effect for skyrmion-based applications.